Inhibition of Clotting as the Result of Plasminogen Activation by Streptokinase - Beller, F. K; Glas, P (Thrombosis and Haemostasis, 1960)
Investigations of the clotting mechanism were carried out by lysis time determinations when plasminogen was activated by streptokinase and the following results were obtained:1. The recalcification time during the period of activation showed an initial decrease of the clotting time, followed by a prolongation.The thrombin time method showed only a prolongation up to the moment when inhibition of coagulation occurred.2. The clotting factors II, V, VII, VIII and IX remained unaffected in this system.3. The clotting activity, as well as the time required for the inhibition of coagulation, were dependent on the streptokinase concentration on the one hand, and on the fibrinogen concentration on the other.4. An antithrombin-like inhibitor could be excluded as the cause of incoagulability.5. In our system, inhibition of coagulation was caused by fibrinogenolysis, by which fibrinogen was altered to a biologically inactive globulin. The latter could still be demonstrated in large amounts by means of certain protein estimations. But the proteolytic activity is assumed to be not strong enough to destroy the other clotting factors as well.This system is, therefore, especially useful for studying the isolated “anti-fibrinogenic“ effect of plasmin.